Comparative studies of the 2νββ decay - Civitarese, Enrique Osvaldo (1998)
The microscopic description of nuclear double beta decay transitions is presented in the framework of a schematic model. The comparison between these results and the ones corresponding to realistic calculations shows that the physics of the double beta decay may be dominated by non-perturbative effects.